Al- Kulini and his Book, Al- Kafi: Presentation and Criticism - al-Omari, Mohammed bin Abdullah (Journal of Islamic Sciences, 2018)
Because Abu Jaafar Al- Kulini and his book known as "Al- Kafi" influenced the doctrine and thought of Imamate Shia, this study aimed at clarifying the meaning of the Twelver Shia, as well as clarifying the suspicions raised about the personality of Al- Kulini and how to deal with it. Moreover, the study aimed at revealing the reason for the absence of any mention of the author of the book, Al- Kulini. The study also aimed to defend the book of Allah and the Prophet Muhammad, peace and blessings be upon him, by denying the fabrications that were said about each of them by some narrators who their goal was not sound good. The researcher followed the method of inductive and analytical approach, where he read the biography of the Al- Kulini and follow in most of the sources of Shia that have been translated to him or his book in addition to reading research and private letters composed of him or his book. The study concluded that the personality of Al- Kulini is not the great personality portrayed by each of his followers of the Shiites, since the phrases in which the mention of the Al- Kulini in the books of some scholars of history and translations of the Sunnis do not indicate what the followers of the Twelver Shia of each reader in the maximization of personality of Al- Kulini, and the inferred by the accuracy, and the book of Al- Kafi contains the spelling and falsification, and it was noted that the influence of Al- Kulini some of the beliefs of non- Muslims. Moreover, the study also concluded that the doctrine of the Imamate in Al- Kulini is based on the case of the text and on the artificial narrators in his sufficient book.
Keywords: Twelver Shia; Al- Kafi; Al- Kulini; suspicions